Radical political theology: religion and politics after liberalism - Crockett, Clayton (Insurrections: critical studies in religion, politics, and culture, 2011)
Introduction: the freedom of radical theology after the death of God -- The parallax of religion: theology and ideology -- Sovereignty and the weakness of God -- Baruch Spinoza and the potential for a radical political theology -- Carl Schmitt, Leo Strauss, and the theo-political problem of liberalism -- Elements for radical democracy: plasticity, equality, and governmentality -- Law beyond law: Agamben, Deleuze, and the unconscious event -- Radical theology and the event: St. Paul with Deleuze -- Plasticity and the future of theology: messianicity and the deconstruction of Christianity -- Conclusion: six theses on political theology